Perovskite Solar Cells: Imaging Spatial Variations of Optical Bandgaps in Perovskite Solar Cells (Adv. Energy Mater. 7/2019). Issue 7 (14th February 2019) - Chen, Boyi; Peng, Jun; Shen, Heping; Duong, The; Walter, Daniel; Johnston, Steve; Al‐Jassim, Mowafak M.; Weber, Klaus J.; White, Thomas P.; Catchpole, Kylie R.; Macdonald, Daniel; Nguyen, Hieu T.
Abstract : In article number1802790, Daniel Macdonald, Hieu T. Nguyen, and co‐workers develop a fast, non‐destructive, camera‐based method to capture optical bandgap images of perovskite solar cells with micron‐scale spatial resolution. This technique allows them to probe relative variations in optical bandgaps across various solar cells, and to resolve optical bandgap inhomogeneity within the same device due to material degradation and impurities. The results are independently confirmed with other optical‐based techniques.